Occult hepatitis B infection among individuals belonging to the aboriginal Nicobarese tribe of India - Bhattacharya, Haimanti; Bhattacharya, Debdutta; Roy, Subarna; Sugunan, Attayur Purushothaman (The Journal of Infection in Developing Countries, 2014)
Introduction: The long-lasting persistence of hepatitis B virus (HBV) genomes in the liver (with or without detectable HBV DNA) of individuals with negative for HBV surface antigen (HBsAg) is termed occult HBV infection (OBI). The present study is a part of the follow up on efficacy of vaccination, 10 years post inception, and was designed to understand the prevalence of Occult Hepatitis B infection (OBI) among the aboriginal Nicobarese tribal community. Methodology: A total of 612 serum samples were collected and tested for various markers including HBsAg, Anti-HBs, Anti-HBc and HBV DNA. Part of S gene of the extracted HBV DNA was amplified by nested PCR. The amplified products were then subjected to sequencing. Genotyping was performed on the basis of phylogenetic relationship along with representative reference sequences from different sub genotypes. Results: The study revealed OBI in 11.1% of the people belonging to the Nicobarese tribe. Phylogenetic analysis showed only one genotype, HBV/D circulating among the Nicobarese population with ayw3 was the major serotype detected. Single or multiple amino acids substitutions were found in 5 of 34 samples (14.7%) which includes I110T, P120T, P/T127I, A128P, M133L and G159V. Conclusions: The detection of OBI among these aboriginal tribes is of great concern and stresses the need for the continuous surveillance as it may contribute to the progression of liver disease to a more advanced stage.